Foodborne hazards in the scientific literature: Results of a systematic literature review in East African countries - Alonso, Silvia; Ocaido, M.; Carron, M.; Roesel, Kristina; Grace, Delia (International Livestock Research Institute, 2015)
Introduction We conducted systematic literature reviews (SLR) of zoonotic hazards (including foodborne hazards) in two main value chains: the dairy value chain in Tanzania and the pork value chain in five countries in East Africa. The SLR sought to extract data and information related to the prevalence, risk factors, control and impacts of a list of hazards in each value chain. Materials The review was conducted through systematic searches in four online databases (PubMed, Cab direct, Web of Science, and Africa journals online), using pre-determined search criteria. Data were extracted using a standardized data form. The SLRs included 10 foodborne hazards in the dairy value chain in Tanzania and 18 foodborne hazards in the pork value chain in East Africa. Results Compared to other zoonotic hazards, foodborne hazards were under-represented in the published literature. Most literature focused on prevalence and risk factor studies, with very few papers investigating control options and impact. The scarcity of publications, linked with the diversity of methods used and inconsistent scientific reporting makes it difficult to combine results. In Tanzania, most literature focused on Brucella and Mycobacterium bovis. Although the dairy value chain includes many players and supply steps, most studies focused on the farm and retailer levels, with very few including consumers. Wildlife was the focus of some studies, primarily looking at their role as pathogen reservoirs. Presence of relevant foodborne hazards was confirmed at retailer level, suggesting potential risk for milk consumers. In the pork value chain, porcine cysticercosis was the most frequently studied foodborne hazard. Studies on important pork related parasites (e.g. T. hydatigena and Trichinella) are lacking in East Africa. Studies on humans have focus on Toxoplasma gondii, but its relation to pork consumption has not been investigated. Other important pork related hazard such as Salmonella are also lacking in the scientific literature. Many of the studied hazards were not the focus of any of the published reports, despite its presence in humans is well known in the target countries. Conclusion Reasons for the underrepresentation of foodborne hazards in the literature are discussed and suggestions for expanded investigation and reporting presented.